Case Report: Winkelmann hip rotationplasty as a last-resort solution - Robin Evrard; Othmane Miri; Valérie Lacroix; Pierre-Louis Docquier; Thomas Schubert (Frontiers in Surgery)
BackgroundRotationplasty, an invasive surgery, serves as an alternative to amputation in pediatric orthopedic oncology. It is currently applied in broader cases (e.g., infection, trauma, or malignant tumors). Winkelmann Type BII rotationplasty is a rare procedure with limited literature. Furthermore, no description of rotationplasties where the femur is attached to the sacroiliac joint has been published to date.MethodsBetween September 2022 and March 2023, three patients underwent Type BII rotationplasty. We used the Clavien-Dindo classification to describe postoperative complications and the musculoskeletal tumor society score (MSTS) for functional result assessments.ResultsOne patient suffered from multiple complications during the first 6 months postoperatively, one presented a single complication, and one had no complications after 4 and 3 months postoperatively, respectively. Two patients could walk pain-free with the help of crutches. One patient developed a crack on the femur, which did not require surgical revision. They all achieved satisfactory joint amplitudes of at least 50° in passive hip flexion. Unfortunately, one of the patients suffered from lung metastases.ConclusionsWinkelmann's Type BII rotationplasty is a reliable alternative to hindquarter amputation. Furthermore, we demonstrated that complete resection of the iliac wing and femur fixation through the sacroiliac joint is feasible.